(untitled) (Research, Society and Development, 2021)
The search for functional foods increases the consumption of the grape and makes it the object of scientific studies, considering the benefits it can provide to human health. Thus, the work aims to describe the functionalities linked to the consumption of the grape (Vitis vinifera), the mechanisms of action and the relationship of the main active compounds present in the fruit. As a methodology, bibliographic research was carried out in the databases, Scielo, Capes Periodicals, Microsoft Academic Search, Scopus and ScienceDirect. It is descriptive research, with approaches that detail the characteristics and specifications from the vine, fruit (peel, pulp and seeds), by-product, bioactive compounds, chemical composition and functionalities. As a result, phenolic compounds were identified in high quantities, the most relevant being flavonoids, stilbenes, phenolic acids and a variety of tannins. Flavonoids, with a higher content, are present in the grape seed, have an antioxidant action and act in the defense of plants against environmental and animal actions, such as: viruses, insects, fungi, bacteria, UV rays and reductions in plant hormones. Stilbene has biological and therapeutic action, such as phytoalexins, and especially resveratrol, which acts in the fight against diseases, especially cardiovascular ones. The tannins, on the other hand, act in plant protection in fight with pathogens. It is concluded that the grape has several functional antioxidants, anti-inflammatory, antimicrobial and anticarcinogenic properties, and this study is relevant for further research on the subject, in view of the benefits obtained by consuming the fruit.